Dental hybrid cone beam CT effective and organ doses. (September 2016) - Loria, A.; Gigliotti, C.R.; Branchini, M.; De Cobelli, F.; Maschio, M. Del; Vecchio, A. del
Abstract : Introduction: Dental hybrid 3D Cone Beam CT (CBCT) NewTom VGi Evo it is a pure CT scan and, due to the possibility to choose a wide range of exposition parameters, is suitable for maxillofacial and otorhinolaryngology surgery. This particular model allows a real 2D acquisition and not only a two-dimensional reconstruction of a 3D image. Purpose: The aim of this study is to provide organs and body effective dose measurements in order to optimize the exposure protocols for every clinical application. Materials and methods: 42 thermo-luminescent dosimeters were placed throughout six layers of the head and neck of a tissue-equivalent phantom, identifying 16 most important OAR. Three field of radiation, corresponding to three areas of interest (maxillofacial, otolaryngology and dental), were considered. The largest field, 24 × 19 cm 2, was available only in Standard Quality modality, while fields 12 × 8 cm 2 and 5 × 5 cm 2 were investigated also with their High-Resolution (HR) modality. Doses delivered by two-dimensional CBCT panoramic view modality and by a digital orthopantomograph exam were compared. Results: In the worst exposition condition (maxillary 3D scan), effective dose resulted 0.14 ± 0.02 mSv, 0, 07 ± 0, 03 mSv for otorhinolaryngology 3D scan and 0, 05 ± 0, 03 mSv for dental. Effective doses for 2D panoramic modality with CBCT and OPT resulted respectively 0.07 ± 0.02 mSv and 0.03 ± 0.02 mSv. Conclusion: The clinical applications involve very different radiation doses. We can provide accurate dosimetric information to clinicians for each exposition possibilities, in order to allow the best choice for every patient. It is important to choose HR modality only if necessary and traditional OPT should not be replaced by CBCT. Disclosure: There is not conflict of interest to declare.